Vascular Endothelial Glycocalyx Plays a Role in the Obesity Paradox According to Intravital Observation - Mitsuda, Shingo; Uzawa, Kohji; Sawa, Marie; Ando, Tadao; Yoshikawa, Takahiro; Miyao, Hideki; Yorozu, Tomoko; Ushiyama, Akira (Frontiers in Cardiovascular Medicine, 2021)
According to the “obesity paradox,” individuals with obesity may be associated with higher survival rates than those who are lean for severe conditions. However, the physiological basis behind the mechanism of the obesity paradox remains unknown. We hypothesize that the glycocalyx in obese mice is thicker and more resistant to inflammatory stress than that in non-obese mice. This study employed intravital microscopy to elucidate differences in the vascular endothelial glycocalyx among three groups of mice fed diets with different fat contents. Male C57BL/6N mice were divided into three diet groups: low-fat (fat: 10% kcal), medium-fat (fat: 45% kcal), and high-fat (fat: 60% kcal) diet. Mice were fed each diet from three weeks of age, and a chronic cranial window was installed at eight weeks of age. At nine weeks of age, fluorescein isothiocyanate-labeled wheat germ agglutinin was injected to identify the glycocalyx layer, and brain pial microcirculation was observed within the cranial windows. We randomly selected arterioles with diameters of 15–45 µm and captured images. The mean thickness of the glycocalyx was calculated using image analysis and defined as the glycocalyx index. The glycocalyx indexes of the high-fat and medium-fat diet groups were significantly higher than those of the low-fat diet group (p < 0.05). There was a stronger positive correlation between vessel diameter and glycocalyx indexes in the high-fat and medium-fat diet groups than in the low-fat diet group. The glycocalyx indexes of the obese groups in the non-sepsis model were higher than those in the control group for all vessel diameters, and the positive correlation was also stronger. These findings indicate that the thickness of the original glycocalyx may play an important role in the obesity paradox.